Rapid water-rock interactions evidenced by hydrochemical evolution of flowback fluid during hydraulic stimulation of a deep geothermal borehole in granodiorite: Pohang, Korea. (December 2019) - Burnside, Neil M.; Westaway, Rob; Banks, David; Zimmermann, Günter; Hofmann, Hannes; Boyce, Adrian J.
Abstract: Flowback water from the 4215 m deep (True Vertical Depth) PX-1 borehole, following the August 2017 hydraulic stimulation of a granodiorite geothermal reservoir in Pohang, South Korea, was monitored for a suite of physicochemical, chemical and isotopic parameters. The results provide unique insights into mixing processes, fluid evolution and rapid water-rock interaction in a deep geothermal system. Injected water for stimulation was relatively fresh, oxidising surface water, with temperature 29.5 °C and pH c. 6.5. The flowback water showed an increasing content of most solutes, with the evolution conforming to an exponential 'flushing' model for conservative solutes such as chloride. Flowback water became progressively Na–Cl dominated, with a circumneutral pH (7.1) and negative oxidation-reduction potential (c. −180 mV). Some solutes (including, Na, K and Si) increased more rapidly than a flushing model would suggest, implying that these had been acquired by the flowback water due to mineral hydrolysis. Stable isotopes of O and H indicate that initially meteoric waters have undergone geothermal oxygen isotope exchange with minerals. Evolution of redox species in recovered water suggests progressively oxidising zonation around the injection borehole in an otherwise reducing reservoir. Rapidly increasing silica concentrations in flowback water suggests extensive quartz dissolution and indicated a reservoir temperature of up to 169 °C. This lends plausible, if equivocal support to the hypothesis that quartz dissolution by injection water may have contributed to triggering movement on the pre-stressed fault associated with the November 2017 Mw 5.5 Pohang earthquake. Highlights: Unique hydrochemical dataset from hydraulic stimulation of a granitic Enhanced Geothermal System. Evolution of flowback fluid chemistry follows that of an exponential 'flushing tank model'. Normalised concentrations of Cl, NH4, As, B, Br, Ca, Mo and Sr exhibit quasi-conservative behaviour. Sodium and potassium show slight initial excess concentrations, suggesting hydrolysis of silicate minerals in the rock matrix. Surplus silicon indicates quartz dissolution by injection water, supporting theory that EGS activity triggered 2017 Mw 5.5 Pohang earthquake.